2000
DOI: 10.1088/0954-0083/12/1/308
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Thin-Film/Lacquer Coatings for Space Applications

Abstract: Thin-film coatings have the capability of obtaining a wide range of thermal radiative properties, but the development of thin-film coatings can sometimes be difficult and costly when trying to achieve highly specular surfaces. Given any space mission’s thermal control requirements, there is often a need for a variation of solar absorptance (αs), emittance (∊) and/or highly specular surfaces. The utilization of thin-film coatings is one process of choice for meeting challenging thermal control requirements beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Other similar measurements [31,32] also measure specularity of 0.98 or higher. For this paper, the collector and secondary used 0.98, whereas the director used 0.94 in recognition of the fact that it may be more difficult to get a highly specular surface in the form of a thin metal foil.…”
Section: G Specularitymentioning
confidence: 85%
“…Other similar measurements [31,32] also measure specularity of 0.98 or higher. For this paper, the collector and secondary used 0.98, whereas the director used 0.94 in recognition of the fact that it may be more difficult to get a highly specular surface in the form of a thin metal foil.…”
Section: G Specularitymentioning
confidence: 85%
“…Peters et al demonstrated good results of tailoring of thin‐film/lacquer coatings for space applications where highly specular surfaces are needed. These coatings can be applied to both rough and smooth substrates.…”
Section: Recent Advancesmentioning
confidence: 99%
“…Traditional conductive coatings, such as metals and indium tin oxides, are sputtered or deposited as thin films onto flexible substrates such as polyimide for spacecraft applications 28–33 . Conductive metals such as copper, silver, and aluminum are used in spacecrafts, and their conductivity degrades when exposed to AO in LEO 34,35 .…”
Section: Introductionmentioning
confidence: 99%